Marketing Strategy of Non-Bank Islamic Financial Institutions to Enhance Financial Inclusion in Indonesia - Irwandi, Irwandi; Arifin, Asriadi (El-kahfi | Jurnal Ekonomi Islam, 2025)
Financial inclusion remains a major challenge in the Indonesian economic system, particularly for low-income communities and micro-entrepreneurs who are not yet served by formal financial institutions. This gap creates unequal access to financial services that can promote economic welfare and social empowerment. This study aims to analyze the role of Non-Bank Islamic Financial Institutions (LKSNB) in expanding financial inclusion in Indonesia and identify effective strategies implemented to reach marginalized groups. The research method used is library research with a qualitative descriptive-analytical approach, through a systematic review of scientific literature, financial institution reports, and related empirical research results. The analysis is conducted using a theoretical framework of financial inclusion based on Islamic economic values, which emphasize distributive justice, the principle of mutual assistance (ta'awun), and Islamic financial ethics. The results show that LKSNB has a strategic role in expanding access to Islamic finance through microfinance products, productive zakat and waqf institutions, and Islamic cooperatives. The practical implications of these findings underscore the importance of government policy support in strengthening the non-bank Islamic financial ecosystem through digitalization, Islamic financial literacy, and collaboration between regulators, Islamic scholars, and industry players. This research is expected to serve as a reference for policymakers and practitioners in designing equitable and sustainable financial inclusion strategies.